An open‐label, investigator‐initiated, single‐center, prospective, pilot clinical study to evaluate the efficacy of a skin whitening serum applied twice daily combined with a spot‐preventing SPF50+ sunscreen in healthy female subjects with melasma hyperpigmentation. (25th June 2021) - Cantelli, Mariateresa; Ferrillo, Maria; Granger, Corinne; Fabbrocini, Gabriella
Abstract: Background: Melasma is a common skin disorder characterized by alterations in normal skin pigmentation. The objective was to evaluate the efficacy and safety of a skin whitening serum containing niacinamide, hydroxyphenoxy propionic acid, dipotassium glycyrrhizate, glycolic acid, and 4‐n‐butylresorcinol applied twice daily combined with a spot‐preventing SPF50+ sunscreen for treatment of melasma. Methods: Twelve healthy Caucasian women with melasma (Fitzpatrick skin types II−IV) were enrolled in this pilot clinical study. Efficacy evaluations were performed at baseline and weeks 4, 8, and 12 of treatment and included clinical and instrumental assessments. Results: All endpoints for melasma hyperpigmentation showed a statistically significant improvement from baseline to the end of the study. There was only one dropout. No signs of irritation or discomfort were observed at baseline, w4, w8, or w12. An overall improvement in melasma was observed both clinically and on reflectance confocal microscopy (RCM). Conclusion: This topical skin whitening serum had favorable outcomes for the treatment of melasma hyperpigmentation in adult women, as demonstrated on investigator and instrumental assessments. The results of this pilot study need to be confirmed in randomized, controlled studies with a larger sample size.